Ethical concerns in Telemedicine- An Indian perspective - Anjankar, AJ; Anjankar, VP; Anjankar , A; Waghmode, A; Ninave , SV (Journal of Indian Academy of Forensic Medicine, 2024)
Telemedicine is the welcome evolution of health care delivery initiated by phenomenal advances in digital communication technology. Improved access, delivery and reduced health care cost can be considered the gold standard of telemedicine which has come a long way both in terms of quality health care and acceptance at all levels in countries like India. Telemedicine has immense potential and promise and offers innumerable opportunities and is set to revolutionize the traditional health care delivery. However, there are certain issues, concerns and challenges which are usually encountered in the beginning of any innovative approach and are likely to be faced during practice of telemedicine. The important ethical concerns include protection of autonomy of the patient, his right to privacy, confidentiality and non-disclosure of sensitive data, issues of ownership and right to its access, sound doctor patient relationship, establishment of duty of care and its standard and issues revolving around liability of doctors. These issues are of immense importance and need immediate attention and hence, this effort to discuss them within the scope of Telemedicine Practice Guidelines along with existing legal provisions controlling medical profession and practice in India and other relevant guidelines and other binding provisions including laws related to information technology.